Price Efficiency and Short Selling - Saffi, Pedro A. C.; Sigurdsson, Kari (Review of Financial Studies, 2011)
This article presents a study of how stock price efficiency and return distributions are affected by short-sale constraints. The study is based on a global dataset, from 2005 to 2008, that includes more than 12,600 stocks from 26 countries. We present two main findings. First, lending supply has a significant impact on efficiency. Stocks with higher short-sale constraints, measured as low lending supply, have lower price efficiency. Second, relaxing short-sales constraints is not associated with an increase in either price instability or the occurrence of extreme negative returns.